Otorgamiento de medidas de protección en el proceso de violencia intrafamiliar y su aplicación en la tutela judicial efectiva. - Mesías Pazmiño, Jeonatan Fernando (2024)
The present research work, in summary, seeks to clarify what the jurisprudence of the Constitutional Court of Ecuador has indicated regarding effective judicial protection as a right and, with this, compare whether it has been used effectively in Ecuadorian society. correct in crimes against women, determine the protection measures against the violation of the right to the presumption of innocence in crimes of domestic violence, the legal and doctrinal concepts are analyzed, study; and, how protection measures are established in the right to the presumption of innocence in crimes of domestic violence in the context of comparative law. The methodology was developed from documentary research, which focused on the positivist interpretive paradigm with a descriptive, exploratory and explanatory level. To do this, synthetic analysis methods, legal doctrine, and hypothetical inferences were used, which allowed the elaboration of analyzes and conclusions regarding the approach to the topic. It was concluded that the judge, in order to decree any protection measure within a domestic violence process, must carefully evaluate the conditions of the specific case in order to verify in which cases a measure is appropriate and when it is not. Finally, it was recommended to all judicial, police, investigative or administrative authorities that carry out an investigation against any citizen who must guarantee the principle of presumption of innocence in each of the phases of the process.